SISTEM PENDUKUNG KEPUTUSAN REKOMENDASI PENGEMBANGAN KARIR DAN PROMOSI JABATAN STRUKTURAL MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) (INTI TALAFA, 2023)
One of the authorities possessed by The Employment Agency Education and Training of Tegal District is Career Development and Promotion Activity. There are many obstacles in carrying out this activity, such as the large number of employee data and the data processsing is still manual, resulting a complex decision-making process and takes a lot of time. In addition, the formulation used is still not suitable with the mandate of PP Number 17 of 2020 concerning the merit system approach to ASN management. The merit system is an ASN policy and management based on qualifcations, copetence, and performance. In this study, the authors create a support system (SPK) with The Simple Additive Weighting SAW method which will facilitate and save time in providing ASN nomination and reccomendation in the career development and promotion process.This research method applies the Research and Development (R&D) method. This method choosen because it is compatible with the software development cycle or SDLC waterfall.